Why Don't Restaurants Want to Promote Their Sustainability? Insights From New Zealand - Koupaei SN; Ballantine PW; Ozanne L (John Wiley and Sons Ltd on behalf of International Journal of Tourism Research, 2025)
Restaurants are increasingly promoting their sustainability attributes. However, this research fills a notable gap in knowledge in relation to the online promotion of sustainability by restaurants in non-Michelin award countries, and where there is no specific sustainable restaurant certification to identify the online promotion of sustainability attributes. The websites of 164 award-winning or nominated New Zealand restaurants were subject to content analysis. Results showed that seasonal and local produce were the most widely promoted sustainability measures. Unlike international sustainable restaurant schemes, there was little emphasis on sustainably harvested fish, Fairtrade, and animal ethics. However, interviews with restaurant chefs, managers, and owners demonstrated that many restaurants do not promote their sustainability practices because of greenwashing concerns and their personal values. The results highlight the online promotion of restaurant sustainability practices and the extent of sustainability practices outside of formal certification or award systems.
Keywords: green hushing; green restaurants; online restaurant marketing; sustainable hospitality; sustainable restaurants; website content analysis